Suicide : Laura Dolce ; introduction by C. Everett Koop. - Dolce, Laura (New York : Chelsea House, 1992)
Discusses the social, psychological, medical, and historical facets of suicide, describing warning signs, risk factors, prevention, and other aspects.
Includes bibliographical references (p. 99-102) and index.
Voice of Youth Advocates (V.O.Y.A.).
Wilson's Junior High School.
7-9
Young Adult
Keywords: Suicide -- Juvenile literature; Suicide; Suicide